Respiratory viruses Ct values and association with clinical outcomes among adults visiting the ED with lower respiratory tract infections - Ines Bentahar; Paul Loubet; Florian Salipante; Christophe Choquet; Diane Descamps; Benoit Visseaux; Nathan Peiffer Smadja; Quentin Le Hingrat; Donia Bouzid (PLoS ONE, 2025)
Background The correlation between real-time PCR (rt-PCR) cycle threshold (Ct) values for respiratory viruses and clinical outcomes remains unclear. This study evaluates the association between Ct values and clinical outcomes in patients tested via point-of-care testing upon emergency department (ED) admission. Methods This is a retrospective analysis of adults admitted to a French university hospital ED for suspected lower respiratory tract infections (LRTI) requiring oxygen therapy between 2019 and 2020. Ct values were assessed for their association with symptom duration and clinical outcomes (hospital length of stay (LOS), Intensive Care Unit (ICU) admission, and 28-day mortality) using zero-inflated negative binomial regression (ZINB) and logistic regression models, adjusted for age, sex, co-infection, and symptom duration. Results A total of 410 patients were included, with 37 (9%) having co-infections with two pathogens and 2 (0.5%) with three pathogens. The most common pathogens were human rhinovirus/enterovirus (HRV/EV) (26.3%), influenza A (24.9%), and SARS-CoV-2 (21.9%). Median symptom duration was 3 days [IQR: 2–7]. Of the patients, 308 (75.1%) were hospitalized, 74 (18%) required ICU care, and the 28-day mortality rate was 11.7% (n = 48). Multivariable analysis showed that higher Ct values for SARS-CoV-2 were associated with reduced odds of hospitalization (OR = 0.75, p = 0.04) and shorter LOS (x0.96 days per Ct unit increase, p = 0.04). Similar trends for shorter LOS were observed for HRV/EV and RSV but did not reach statistical significance. Conversely, higher influenza A Ct values were linked to longer LOS (x1.05 days per Ct unit increase, p = 0.025). Higher Ct values for SARS-CoV-2 were also associated with lower 28-day mortality (OR = 0.87, p = 0.049). Ct values were not associated with ICU admission for any virus. Conclusion This study supports the association of higher Ct values with shorter LOS and lower mortality for SARS-CoV-2. In contrast, higher Ct values for influenza A were linked to longer LOS. Ct values were not predictive of ICU admission, underscoring the complexity of the relationship between viral load and clinical outcomes.